THE EFFECT OF DIGITAL-BASED TALENT MANAGEMENT ON ACADEMIC PERFORMANCE THROUGH DIGITAL COMPETENCE - Dewi Budhiartini Yuli Isnaini; Putra Chairy (RADJA PUBLIKA, 2026)
Digital transformation has significantly reshaped higher education, requiring universities to develop effective strategies for enhancing students’ academic outcomes. However, empirical evidence regarding how digital-based talent management improves academic performance through digital competence remains limited, particularly in emerging economy contexts. This study aims to examine the direct and indirect effects of digital-based talent management on students’ academic performance, with digital competence serving as a mediating variable. Drawing upon Human Capital Theory and the Technology Acceptance Model (TAM), data were collected from 200 students of Universitas Islam Sumatera Utara and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital-based talent management has a positive and significant effect on both digital competence and academic performance. Digital competence also significantly influences academic performance and partially mediates the relationship between digital-based talent management and academic performance. Furthermore, the indirect effect through digital competence is stronger than the direct effect, highlighting the importance of capability development in achieving academic success. These findings contribute to the literature by integrating institutional strategy and individual capability within a comprehensive framework and provide practical implications for universities seeking to enhance academic performance through structured digital talent development initiatives.